ASAM KLOROGENAT PADA KOPI DAN OBESITAS: A SYSTEMATIC REVIEW Chlorogenic Acid in Coﬀee and Obesity: A Systematic Review - Kamila Dwi Febrianti; Stefania Widya Setyaningtyas (Media Gizi Indonesia, 2021)
Obesity are defined as excessive fat accumulation caused of imbalance energy in and energy out. Consuming a cup of coﬀee can help prevent obesity through chlorogenic acid compound. Chlorogenic acid is one of biactive component that has an important role to our body. Chlorogenic acid has a potential role in body weight reduction and preventing obesity. Chlorogenic acid has an eﬀect to inhibit the absorption of glucose in the intestine, block the conversion     of glucose to fat in the adipose tissue and protect from weight gain. Chlorogenic acid that contain in coﬀee has a diﬀerences that depend on variety, type, roasting duration, temperature and coﬀee bean size. Based on several studies, giving chlorogenic acid as a form of supplementation or green coﬀee extract has demonstrated a consistent result. Those studies explain that chlorogenic acid in coﬀee can inhibit body fat accumulation and reducing body weight. The aim of this systematical review was to know the contain of chlorogenic acid in coﬀee and analyze the eﬀect of giving chlorogenic acid to obesity. The experimental studies in human and animal subjects in the last 15 years as inclusion criteria and studies that is not represent the anthropometry result as exclusion criteria through electronic database were comprehensively reviewed. The result from five studies demonstrated that chlorogenic acid has an eﬀect to reduce body weight, reduce body fat percentage, and reduce blood glucose concentration with the duration and chlorogenic acid dosage diﬀerently. Chlorogenic acid has many benefits in improving the obesity.